Atypical Case of VV1 Creutzfeldt–Jakob Disease Subtype: Case Report - Carrasco, Adrianna E.; Appleby, Brian S.; Cali, Ignazio; Okhravi, Hamid R. (Frontiers in Neurology, 2022)
Creutzfeldt–Jakob disease (CJD) is a rare form of rapidly progressive, neurodegenerative disease that results from the misfolding and accumulation of an aberrant, disease-associated prion protein (PrPD). CJD affects 1–1.5 cases per million per year with the sporadic-type accounting for an estimated 85% of these cases. Sporadic CJD (sCJD) is further subdivided into five subtypes based on genetic polymorphisms; the rarest subtype, sCJDVV1, occurs at a rate of 1 case per one-hundredth million population per year. Clinical characteristics of the sCJDVV1 subtype have been reported to show, early age of onset (44 years), average disease duration of 21 months, absent PSWCs on electroencephalography (EEG), and MRI hyperintensities in the cerebral cortex with usual negative signal in the basal ganglia or thalamus. We present a case of the sCJDVV1 subtype with uncommon features. Contrary to current data on sCJDVV1, our patient presented with an unusual age at onset (61 years) and longer disease duration (32 months). The highly sensitive and specific real-time quaking-induced conversion (RT-QuIC) assay was negative. Presenting clinical symptoms included paranoid thoughts and agitation, rapidly progressive memory decline, prosopagnosia, and late development of myoclonus and mutism. Other findings showed positive antithyroid peroxidase antibodies (anti-TPO), and absent PSWCs on EEG. High-dose steroid therapy treatment was administered based on positive anti-TPO findings, which failed to elicit any improvement and the patient continued to decline. To our knowledge, only four cases with the sCJDVV1 subtype, including our patient, have been reported to have a negative result on RT-QuIC. This may suggest varied sensitivity across sCJD subtypes. However, given the rarity of our patient's subtype, and the relatively novel RT-QuIC, current data are based on a small number of cases and larger cohorts of confirmed VV1 cases with RT-QuIC testing need to be reported.